Knowledge and practices: actions to promote breastfeeding developed by the nursing team: integrative review (Research, Society and Development, 2021)
Introduction: The encouragement of breast-feeding (AM), corresponds to a strategy of great need, while making the link, affection, protection and nutrition of the child natural. Objective: The general objective is to conceptualize the breast-feeding promotion actions developed by the nursing team.Methodology: Integrative review, with a qualitative approach, of an exploratory nature.Results: The nurse should identify during prenatal care the pregnancy's knowledge, practical experience, beliefs and social and family experience with the aim of promoting health education for breast-feeding, as well as ensuring vigilance and effectiveness during postpartum nutrition care.Final considerations: Nursing has made a major contribution when it comes to supporting the practice of breast-feeding and raising awareness of early weaning, because it has practical and theoretical knowledge to opportune educational moments,It guides pregnant women and workers on the importance of breast-feeding and the correct management of lactation.